Gambaran Intervensi Penghentian Merokok Pada Pasien Tuberkulosis Yang Resisten Terhadap Obat di RS X - Indrayani, Kantun Safira; Fadhila, Syifa Nur; Qomariah, Siti Nur (Journal of Health Management Research, 2025)
Background: Because of its high recurrence risk and extended treatment duration, drug-resistant tuberculosis (DR-TB) presents a serious public health concern. Poor treatment adherence, financial difficulties, immunocompromised conditions, bacterial mutations, and irregular treatment regimens are some of the factors that lead to recurrence. Aims: To describe smoking cessation intervention in drug-resistant tuberculosis patients at Hospital X. Methods: A qualitative research study explored the challenges of providing Smoking Cessation (SC) interventions in a hospital setting, specifically focused on patients with drug-resistant tuberculosis, hospital staff, and structural elements, with a total sample size of 18. Conducted at a DR-TB management hospital in Surabaya. In-depth interviews lasting approximately thirty minutes each utilized open-ended questions regarding the dangers of smoking, barriers to cessation support, and resource availability. Interviews were recorded, transcribed verbatim, and thematically analyzed using an inductive coding approach following participant consent. Results: The research offers subthemes that were outlined under each of the three main themes (barriers to quitting smoking) that were identified. Individual DR-TB inpatients' personal factors are obstacles to quitting smoking, whereas hospital staff members' personal aspects are obstacles to quitting smoking. The government and hospital administration are in charge of addressing the institutional impediments to quitting smoking. Conclusion: The health of drug-resistant tuberculosis inpatients is adversely affected by cigarette smoking. Mandatory screening and counseling for smokers among DR-TB and TB patients are essential for developing effective treatment strategies in healthcare.